A Comparative Study between Public and Private Housing Finance Companies (HFCs) in India - Prof. S.V Satyanarayana; Mrs. Srilakshmi Ramu (International Journal of Engineering and Management Research, 2019)
A house is a basic necessity, a symbol of security, and a measure of socioeconomic status and pride. In India the policy reforms in the housing sector have led to an increase in the number of banking and non-banking financial institutions providing different types of housing finance services. In this regard, the public (HFCs) and private HFCs are operating at different levels to provide housing finances to all the sections of society. The present study is an attempt to comparatively analyze the financial performance of five public HFCs and five private HFCs in India for the period of 2009-2018. The collected data were analyzed using descriptive statistics in the form of means and a student t-test was conducted to compare the performance of public and private HFCs with regard to various financial ratios. The result showed that profitability, and operating ratios significantly influenced the financial performance of public and private HFCs. The present study calls for regulatory measures and policy reforms to improve the profitability and operating efficiency of both public and private HFCs. This study has an implication in improving the housing finance sector from the perspective of Indian HFCs.